Foods of Ghana - Sheen, Barbara (Detroit : Gale Cengage Learning, 2012)
Looks at the foods of the people of Ghana, including groundnut soup, red-red, and kelewele.
Essential ingredients -- It takes a full stomach to blow a horn -- Tasty treats -- Festive foods.
Includes index.
Keywords: COOKING, GHANAIAN -- JUVENILE LITERATURE